El rebranding como herramienta para el posicionamiento en redes sociales de la U.E. Ecuatoriano Holandés - Villacis Ortiz, Erik Samuel (2024)
This project addresses the need to redesign the image of the Unidad Educativa Ecuatoriano Holandés through a comprehensive rebranding and digital marketing strategy. The goal is to update its visual identity and graphic design elements so that it can adapt to the changing dynamics of the market. This approach includes the distribution of relevant content in order to attract and retain its target audience, thus consolidating a solid relationship with the institution. The development of the project was based on a deductive methodological approach. Through bibliographic and field research, interviews and surveys, valuable information was gathered to guide the rebranding process and the social media marketing strategy. It is recognized that in an ever-changing competitive environment, all brands must adapt to remain relevant. This adaptation can involve anything from minimal adjustments to radical changes, such as a complete brand transformation. In this context, the need arises to explore new strategies to gain visibility in the market, with social networks being a key channel. Therefore, a media schedule was designed in addition to a content plan specifically aimed at platforms such as Facebook, Instagram, TikTok and WhatsApp. These social networks emerge as key tools to reach and engage the target audience, taking advantage of their reach and interaction potential. The goal is to create a dynamic and attractive digital presence that comes to reflect the values and educational excellence of the Unidad Educativa Ecuatoriano Holandés